Enterovirus-A71 Rhombencephalitis Outbreak in Catalonia: Characteristics, Management and Outcome. Issue 7 (July 2021) - Wörner, Núria; Rodrigo-García, Rocío; Antón, Andrés; Castellarnau, Ester; Delgado, Ignacio; Vazquez, Èlida; González, Sebastià; Mayol, Lluís; Méndez, Maria; Solé, Eduard; Rosal, Jaume; Andrés, Cristina; et al.
Abstract : Background: Between April and June 2016, an outbreak of rhombencephalitis (RE) caused by enterovirus (EV) A71 was detected in Catalonia, Spain—the first documented in Western Europe. The clinical characteristics and outcome of patients with this condition differed from those reported in outbreaks occurring in Southeast Asia. Methods: Observational, multicenter study analyzing characteristics, treatment and outcome of patients with EV-A71 rhombencephalitis diagnosed in 6 publicly funded hospitals within the Catalonian Health Institute. A review of clinical characteristics, diagnosis, treatment and outcome of these patients was conducted. Results: Sixty-four patients met the clinical and virologic criteria for rhombencephalitis caused by EV-A71. All patients had symptoms suggesting viral disease, mainly fever, lethargy, ataxia and tremor, with 30% of hand-foot-mouth disease. Intravenous immunoglobulin therapy was given to 44/64 (69%) patients and methylprednisolone to 27/64 (42%). Six patients (9%) required pediatric intensive care unit admission. Three patients had acute flaccid paralysis of 1 limb, and another had autonomic nervous system (ANS) dysfunction with cardiorespiratory arrest. Outcome in all patients (except the patient with hypoxic-ischemic encephalopathy) was good, with complete resolution of the symptoms. Conclusions: During the 2016 outbreak, rhombencephalitis without ANS symptoms was the predominant form of presentation and most patients showed no hand-foot-mouth disease. These findings contrast with those of other patient series reporting associated ANS dysfunction (10%–15%) and hand-foot-mouth disease (60%–80%). Complete recovery occurred in almost all cases. In light of the favorable outcome in untreated mild cases, therapies for this condition should be reserved for patients with moderate-severe infection. The main relevance of this study is to provide useful information for setting priorities, management approaches and adequate use of resources in future EV-A71 associated rhombencephalitis outbreaks.